Prescription non-conformities in primary care settings: How useful are guidelines - Fahad A Al-Hussein (Wolters Kluwer Medknow Publications, 2008)
Background: Apart from having a negative impact on work flow in practice, prescription errors may pose a threat to patient safety. Such errors have been reported in the pharmaceutical services in spite of the clear guidelines issued by the parent organization. Objective: This study was to explore the degree of conformity to the prescribing guidelines at Primary Care level in the Saudi National Guard Health Affairs in Riyadh. Methods: Prescriptions were collected during audits done fortnightly through a simple random selection from a sampling frame of all prescriptions given within the period. Information about each prescription was entered in a database by the pharmacists and each prescription was classified according to its conformity to the guidelines. Information was presented on 330 prescriptions for eleven audits carried out from September 2004 to February 2005. Results: 87% of the prescriptions did not conform to the given guidelines. Less than 1% of the inconsistencies were potentially harmful to the patient, 77.8% had possible negative effect on the pharmacist's work, while 21.3% were unimportant. Patient information was deficient in 16.9% of cases, drug information in 49.6% and archiving/record information related non-conformities constituted 33.5%. Conclusions: Conformity to prescribing guidelines is quite low in spite of the significant input of resources by the parent organization. This burden on work flow, utilization of time and service delivery needs to be studied and addressed by ensuring that there are periodic audits in the work routines of primary health care, and a feedback given to the care providers.